Sorption property of polymer membranes for liquid mixtures. - Lee, Cathrine Hui Min. (2010)
Pervaporation, which is a membrane-based dehydration technique, has received increasing attention in recent years due to its process simplicity, high selectivity and low costs. Compounds which cannot be easily separated by conventional means such as distillation, can be separated using pervaporation. These compounds include isomers, azeotropes and heat sensitive compounds. The sorption properties of the membranes used in pervaporation are critical in determining the success of the pervaporation process. This project studies the sorption properties of the chitosan and polyhedral oligomeric silsesquioxanes (POSS) composite membranes in ethanol solution, with the objective to find any correlation in the degree of swelling and concentration of ethanol sorped by the membranes with the amount of POSS in the chitosan membranes. Four types of POSS derivatives were used; Octa Nitro Phenyl Silsesquioxane (ONPS), Octa Amino Phenyl Silsesquioxane (OAPS), which are hydrophobic and Octa Anion (OA) and Octa Ammonium Silsesquioxane (OAS), which are hydrophilic. Different amounts of the POSS derivatives were incorporated into chitosan membranes. Sorption experiments were then carried out to analyse the sorption properties of the membranes. Due to the volatility of ethanol and the complex interactions between POSS derivatives and chitosan, the results obtained did not show a distinctive trend. However, in general, the incorporation of POSS derivatives into chitosan membranes led to an increase in the degree of swelling and a decrease in the concentration of ethanol sorped. This indicated that the amount of water sorped was higher in the composite membranes. It can be concluded that the sorption performance, and therefore pervaporation, was improved with the incorporation of POSS into chitosan membranes.